Accessory Renal Artery Stenosis and Secondary Hypertension - Ariel A. Chung; Patricia R. Millner (Case Reports in Nephrology)
Background. Secondary hypertension is an uncommon cause of hypertension with extensive workup not recommended in most patients; however, further evaluation is generally recommended in young patients presenting with hypertension. Case Presentation. A 31-year-old female presented with history of elevated blood pressures. Secondary hypertension workup revealed no laboratory abnormalities; however, renal artery ultrasound demonstrated a left superior accessory artery and suspected bilateral renal vein congestion that was further evaluated with renal CT with contrast. Renal CT showed ostial stenosis of the left accessory renal artery. In addition, compression of the left renal vein between aorta and superior mesenteric artery was also noted, consistent with nutcracker syndrome. Hypertension was suspected to be secondary to stenosis of the accessory renal artery. Upon consultation with interventional radiology, pharmacologic treatment was recommended, and blood pressure control was ultimately achieved with a single agent. Discussion. Renovascular etiologies are responsible for 1% of cases of mild hypertension and up to 45% of severe hypertension. Accessory renal arteries are a normal anatomical variant in approximately 30% of the population. Secondary hypertension due to stenosis of an accessory renal artery is rare with very few cases described in case reports. Conclusion. Though hypertension secondary to accessory renal artery stenosis is rare and not well published in medical literature, few case reports, including this one, demonstrate that accessory renal artery stenosis can be an underlying etiology of hypertension.